Question webs-based learning: Science process skills and scientific questioning skills of students on harmonic motion topic - Ammalia Nurjannah; Abdul Gani; Evendi Evendi; Muhammad Syukri; Elisa Elisa (Universitas PGRI Kanjuruhan Malang, 2020)
The success of students in dealing with the globalization era of scientific literacy needs to be supported by practising skills, one of the skills that must be mastered by students in the science process skills and scientific questioning skills. This study aims to determine the implementation of the question webs based learning model of learning to improve science process skills and scientific questioning skills in grade X students at SMAN 1 Darul Imarah using a quasi-experimental method with nonequivalent control group design. The samples were taken by purposive sampling technique which was then divided into experimental and control groups. The data were collected from pretest and posttest scores which were then tested based on N-gain values. The results showed that the score of science process skills and scientific questioning skills of experimental class students obtained higher mean scores than control class mean scores. Statistically, it can be seen that testing the results of tests using the t-test 4.507 for science process skills and 29.79 for scientific questioning skills with a significant difference. The conclusion of this study shows that the question web-based learning model improve science process skills and scientific questioning skills compared to conventional models.